A Digital Ecosystem for the Collaborative Production of Open Textbooks: The LATIn Methodology - Silveira, Ismar Frango; Ochôa, Xavier; Cuadros-Vargas, Alex; Pérez Casas, Alén; Casali, Ana; Ortega, Andre; Sprock, Antonio Silva; Alves, Carlos Henrique; Collazos Ordoñez, Cesar Alberto; Deco, Claudia; Cuadros-Vargas, Ernesto; Knihs, Everton; et al. (Journal of information technology education, 2013)
Access to books in higher education is an issue to be addressed, especially in the context of underdeveloped countries, such as those in Latin America. More than just financial issues, cultural aspects and need for adaptation must be considered. The present conceptual paper proposes a methodology framework that would support collaborative open textbook initiatives. This methodology intends to be the main guideline for a digital ecosystem for the collaborative production of open textbooks and has the potential to solve standing methodological problems of current initiatives, such as Wikibooks and Connexions. The system's architecture and construction will be guided by six collaborative writing dimensions: process, roles, timing, controlling, granularity, and writing groups. Each dimension will coordinate an aspect of the collaborative work and is detailed in the methodology proposed in this paper. This paper is divided in the following parts: the first part introduces the subject, being followed by an analysis of related works about collaboration and Computer-Supported Cooperative Work; in this section, some authors, ideas, and methodological aspects of collaborative writing are also discussed. Next, the paper shows the proposal of a Digital Ecosystem for the collaborative creation of open textbooks, the six dimensions of this Ecosystem, and its respective descriptions. The work finishes with some conclusions about the proposal and the next steps needed to implement it in the real world.